Modelling for water management: first calibration of yield-SAFE for irrigated maize in Mediterranean regions - Palma, J.H.N. (2007)
In the Mediterranean region, careful management of water and nitrogen utilization is required to achieve high crop yields in a sustainable and economic way. Prediction models are useful tools for deriving site/region–specific optimum management strategies for irrigation and nitrogen use. Yield-SAFE, a simple and robust model for growth and resource use in agroforestry systems, simulates crop yields under rainfed and irrigated conditions. This paper represents a refined calibration with respect to the fluxes of water, based on, data from an irrigation/fertilisation experiment with maize in the South-East of Turkey. The model performs satisfactorily and further development will includede nitrogen leaching calibration and validation.